ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NIAT BELI PADA TIKET ONLINE KERETA API DISURABAYA - GOENARDI, SATRIYA BINANGKIT (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2013)
Research conducted aimed to determine the factors that influence consumer purchase intention on train tickets online in Surabaya. Variables used in this study is Trust in online stores, Perceived risk, Perceived ease of use, perceived usefulness, attitude toward online purchasing and Purchase Intention.This study uses SEM (Structural Equation Modeling), sampling technique in this study using a non-probability sampling study that used samples of 150 respondents. Characteristics of the sample are people who've made a purchase train tickets onlineThe results showed that trust in online stores negatively affects perceived risk, perceived risk influences on Attitude toward online purchasing is negative, the effect of Perceived ease of use of the Perceived usefulness is positive. Perceived usefulness positive effect on Attitude toward online purchasing, online purchasing Attitude toward positive effect on Purchase intention.